PERHITUNGAN PENDAPATAN USAHATANI PADI SAWAH IRIGASI POMPA AIR DI KELURAHAN INOBONTO KECAMATAN BOLAANG KABUPATEN BOLAANG MONGONDOW (Calculation of Water Pump Irrigation Rice Farming Income in Inobonto, Bolaang Sub-District, Bolaang Mongondow Regioncy) - Farhansyah Roni Dunggio; Gene H. M. Kapantow; Eyverson Ruauw (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
This study aims to calculate the income of pump-irrigated rice farmers in Inobonto Village. The sampling method used census techniques, the data collected in this study were primary data obtained from direct interviews with respondents through questionnaires or questionnaires and secondary data in the form of other information related to this research through literature studies. The results of this study show that the average farmer income per hectare is Rp. 9,298,464 per planting season and the R/C ratio value of 2.02 indicates that water pump irrigated rice farming in Inobonto Village is already profitable.